Less than 3 doses of the HPV vaccine – Review of efficacy against virological and disease end points. Issue 6 (2nd June 2016) - Basu, Partha; Bhatla, Neerja; Ngoma, Twalib; Sankaranarayanan, Rengaswamy
ABSTRACT: World Health Organization (WHO) recommended 2 doses of the Human Papillomavirus (HPV) vaccine for girls below 15 y on the basis of the immune-bridging studies demonstrating non-inferior immune response of 2 doses in the adolescent girls compared to 3 doses in the young adult women in whom the efficacy against disease is established. The biological nature of the antigens (virus-like particles) constituting the HPV vaccine is responsible for the vigorous antibody response that may make the third dose redundant. The protection offered by 2 doses has been demonstrated in non-randomized clinical trials to be comparable to that offered by 3 doses against incident and persistent infections of vaccine targeted HPV types. However, results emerging from the ecological and nested case-control studies embedded in the population based screening programs of different countries indicate reduced efficacy of 2 doses against virological and disease end points. Some recent studies observed the protective effect of single dose of the vaccine against incident and persistent infections of the vaccine targeted HPV types to be similar to 3 doses in spite of immunological inferiority. The sample size, duration of follow-ups and number of events were limited in these studies. Longer follow ups of the less than 3 doses cohorts in the ongoing studies as well as appropriately designed and ethically justifiable randomized studies are needed to establish the protection offered by the alternative schedules at least beyond 10 y of vaccination.